2014
DOI: 10.6061/clinics/2014(12)05
|View full text |Cite
|
Sign up to set email alerts
|

Neurological status predicts response to alpha-blockers in men with voiding dysfunction and Parkinson's disease

Abstract: OBJECTIVES:To evaluate predictors of the response to doxazosin, a selective alpha-adrenoceptor antagonist, when used for the treatment of lower urinary tract symptoms in men with Parkinson's disease.METHODS:In a prospective study, 33 consecutive men (mean age 59.2±7.0 years) with Parkinson's disease and lower urinary tract symptoms were evaluated. Neurological dysfunction was assessed with the Unified Parkinson's Disease Rating Scale. Urological assessment was performed at baseline and after 12 weeks of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…These drugs are thought to reduce resistance throughout the bladder outlet by relaxing the smooth muscle activity in the prostate, urethra and bladder neck. In a 12 week open label study, Gomez et al found that doxazocin, a selective alpha-adrenoceptor agonist, was associated with significant improvement in LUTS severity and on quality of life [97]. It should be noted that alpha adrenoceptors may worsen or induce orthostatic hypotension in PD.…”
Section: Alpha Eadrenoceptor Agonistmentioning
confidence: 99%
“…These drugs are thought to reduce resistance throughout the bladder outlet by relaxing the smooth muscle activity in the prostate, urethra and bladder neck. In a 12 week open label study, Gomez et al found that doxazocin, a selective alpha-adrenoceptor agonist, was associated with significant improvement in LUTS severity and on quality of life [97]. It should be noted that alpha adrenoceptors may worsen or induce orthostatic hypotension in PD.…”
Section: Alpha Eadrenoceptor Agonistmentioning
confidence: 99%
“…Reflex voiding and voiding by abdominal pressure should be avoided unless the intravesical pressure remains within 40 cmH2O [ 133 ]. Alpha-adrenergic antagonists and urethral sphincter botulinum toxin A injection may be effective in decreasing urethral resistance and improve voiding [ 134 , 135 , 136 , 137 ]. Surgeries such as external sphincterotomy may be considered to reduce urethral resistance in patients’ refractory to conservative treatments.…”
Section: Discussionmentioning
confidence: 99%
“… 11 111 α-Adrenergic blockers (tamsulosin, doxazosin, or terazosin) can be used for the sensation of incomplete bladder emptying and an intermittent urinary stream. 111 119 Phosphodiesterase inhibitors (sildenafil, tadalafil, or vardenafil) are used to treat sexual dysfunction in patients with PD, but they are not generally recommended for patients with cardiovascular disease. 11 111 …”
Section: Genitourinary Disordersmentioning
confidence: 99%